6.16 Problems 1501 to 1600

Table 6.31: Main lookup table sequentially arranged

#

ODE

Mathematica

Maple

1501

\[ {}y^{\prime \prime }+4 y = \operatorname {Heaviside}\left (t -\pi \right )-\operatorname {Heaviside}\left (t -3 \pi \right ) \]

1502

\[ {}y^{\prime \prime \prime \prime }+5 y^{\prime \prime }+4 y = 1-\operatorname {Heaviside}\left (t -\pi \right ) \]

1503

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = k \left (\operatorname {Heaviside}\left (t -\frac {3}{2}\right )-\operatorname {Heaviside}\left (t -\frac {5}{2}\right )\right ) \]

1504

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = \frac {\operatorname {Heaviside}\left (t -\frac {3}{2}\right )}{2}-\frac {\operatorname {Heaviside}\left (t -\frac {5}{2}\right )}{2} \]

1505

\[ {}u^{\prime \prime }+\frac {u^{\prime }}{4}+u = \frac {\operatorname {Heaviside}\left (t -5\right ) \left (t -5\right )-\operatorname {Heaviside}\left (t -5-k \right ) \left (t -5-k \right )}{k} \]

1506

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \delta \left (t -\pi \right ) \]

1507

\[ {}y^{\prime \prime }+4 y = \delta \left (t -\pi \right )-\delta \left (t -2 \pi \right ) \]

1508

\[ {}y^{\prime \prime }+3 y^{\prime }+2 y = \delta \left (t -5\right )+\operatorname {Heaviside}\left (t -10\right ) \]

1509

\[ {}y^{\prime \prime }+2 y^{\prime }+3 y = \sin \left (t \right )+\delta \left (t -3 \pi \right ) \]

1510

\[ {}y^{\prime \prime }+y = \delta \left (t -2 \pi \right ) \cos \left (t \right ) \]

1511

\[ {}y^{\prime \prime }+4 y = 2 \delta \left (t -\frac {\pi }{4}\right ) \]

1512

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \cos \left (t \right )+\delta \left (t -\frac {\pi }{2}\right ) \]

1513

\[ {}y^{\prime \prime \prime \prime }-y = \delta \left (t -1\right ) \]

1514

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{2}+y = \delta \left (t -1\right ) \]

1515

\[ {}y^{\prime \prime }+\frac {y^{\prime }}{4}+y = \delta \left (t -1\right ) \]

1516

\[ {}y^{\prime \prime }+y = \frac {\operatorname {Heaviside}\left (t -4+k \right )-\operatorname {Heaviside}\left (t -4-k \right )}{2 k} \]

1517

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = f \left (t \right ) \]

1518

\[ {}y^{\prime \prime }+2 y^{\prime }+2 y = \delta \left (t -\pi \right ) \]

1519

\[ {}y^{\prime } = 2 y \]

1520

\[ {}x y^{\prime }+y = x^{2} \]

1521

\[ {}y^{\prime }+2 x y = x \]

1522

\[ {}2 y^{\prime }+x \left (y^{2}-1\right ) = 0 \]

1523

\[ {}y^{\prime } = x^{2} \left (1+y^{2}\right ) \]

1524

\[ {}y^{\prime } = -x \]

1525

\[ {}y^{\prime } = -x \sin \left (x \right ) \]

1526

\[ {}y^{\prime } = x \ln \left (x \right ) \]

1527

\[ {}y^{\prime } = -x \,{\mathrm e}^{x} \]

1528

\[ {}y^{\prime } = \sin \left (x^{2}\right ) x \]

1529

\[ {}y^{\prime } = \tan \left (x \right ) \]

1530

\[ {}y^{\prime } = \cos \left (x \right )-y \tan \left (x \right ) \]

1531

\[ {}y^{\prime } = \frac {x^{2}-2 x^{2} y+2}{x^{3}} \]

1532

\[ {}y^{\prime } = x \left (1+y^{2}\right ) \]

1533

\[ {}y^{\prime } = -\frac {y \left (1+y\right )}{x} \]

1534

\[ {}y^{\prime } = a y^{\frac {a -1}{a}} \]

1535

\[ {}y^{\prime } = {| y|}+1 \]

1536

\[ {}y^{\prime } = -\frac {x}{2}-1+\frac {\sqrt {x^{2}+4 x +4 y}}{2} \]

1537

\[ {}y^{\prime }+a y = 0 \]

1538

\[ {}y^{\prime }+3 x^{2} y = 0 \]

1539

\[ {}x y^{\prime }+y \ln \left (x \right ) = 0 \]

1540

\[ {}x y^{\prime }+3 y = 0 \]

1541

\[ {}x^{2} y^{\prime }+y = 0 \]

1542

\[ {}y^{\prime }+\frac {\left (1+x \right ) y}{x} = 0 \]

1543

\[ {}x y^{\prime }+\left (1+\frac {1}{\ln \left (x \right )}\right ) y = 0 \]

1544

\[ {}x y^{\prime }+\left (1+x \cot \left (x \right )\right ) y = 0 \]

1545

\[ {}y^{\prime }-\frac {2 x y}{x^{2}+1} = 0 \]

1546

\[ {}y^{\prime }+\frac {k y}{x} = 0 \]

1547

\[ {}y^{\prime }+\tan \left (k x \right ) y = 0 \]

1548

\[ {}y^{\prime }+3 y = 1 \]

1549

\[ {}y^{\prime }+\left (\frac {1}{x}-1\right ) y = -\frac {2}{x} \]

1550

\[ {}y^{\prime }+2 x y = x \,{\mathrm e}^{-x^{2}} \]

1551

\[ {}y^{\prime }+\frac {2 x y}{x^{2}+1} = \frac {{\mathrm e}^{-x^{2}}}{x^{2}+1} \]

1552

\[ {}y^{\prime }+\frac {y}{x} = \frac {7}{x^{2}}+3 \]

1553

\[ {}y^{\prime }+\frac {4 y}{x -1} = \frac {1}{\left (x -1\right )^{5}}+\frac {\sin \left (x \right )}{\left (x -1\right )^{4}} \]

1554

\[ {}x y^{\prime }+\left (2 x^{2}+1\right ) y = x^{3} {\mathrm e}^{-x^{2}} \]

1555

\[ {}2 y+x y^{\prime } = \frac {2}{x^{2}}+1 \]

1556

\[ {}y^{\prime }+y \tan \left (x \right ) = \cos \left (x \right ) \]

1557

\[ {}\left (1+x \right ) y^{\prime }+2 y = \frac {\sin \left (x \right )}{1+x} \]

1558

\[ {}\left (x -2\right ) \left (x -1\right ) y^{\prime }-\left (4 x -3\right ) y = \left (x -2\right )^{3} \]

1559

\[ {}y^{\prime }+2 \sin \left (x \right ) \cos \left (x \right ) y = {\mathrm e}^{-\sin \left (x \right )^{2}} \]

1560

\[ {}x^{2} y^{\prime }+3 x y = {\mathrm e}^{x} \]

1561

\[ {}y^{\prime }+7 y = {\mathrm e}^{3 x} \]

1562

\[ {}\left (x^{2}+1\right ) y^{\prime }+4 x y = \frac {2}{x^{2}+1} \]

1563

\[ {}x y^{\prime }+3 y = \frac {2}{x \left (x^{2}+1\right )} \]

1564

\[ {}y^{\prime }+y \cot \left (x \right ) = \cos \left (x \right ) \]

1565

\[ {}y^{\prime }+\frac {y}{x} = \frac {2}{x^{2}}+1 \]

1566

\[ {}\left (x -1\right ) y^{\prime }+3 y = \frac {1}{\left (x -1\right )^{3}}+\frac {\sin \left (x \right )}{\left (x -1\right )^{2}} \]

1567

\[ {}2 y+x y^{\prime } = 8 x^{2} \]

1568

\[ {}x y^{\prime }-2 y = -x^{2} \]

1569

\[ {}y^{\prime }+2 x y = x \]

1570

\[ {}\left (x -1\right ) y^{\prime }+3 y = \frac {1+\left (x -1\right ) \sec \left (x \right )^{2}}{\left (x -1\right )^{3}} \]

1571

\[ {}\left (x +2\right ) y^{\prime }+4 y = \frac {2 x^{2}+1}{x \left (x +2\right )^{3}} \]

1572

\[ {}\left (x^{2}-1\right ) y^{\prime }-2 x y = x \left (x^{2}-1\right ) \]

1573

\[ {}x y^{\prime }-2 y = -1 \]

1574

\[ {}\sec \left (y\right )^{2} y^{\prime }-3 \tan \left (y\right ) = -1 \]

1575

\[ {}{\mathrm e}^{y^{2}} \left (2 y y^{\prime }+\frac {2}{x}\right ) = \frac {1}{x^{2}} \]

1576

\[ {}\frac {x y^{\prime }}{y}+2 \ln \left (y\right ) = 4 x^{2} \]

1577

\[ {}\frac {y^{\prime }}{\left (1+y\right )^{2}}-\frac {1}{x \left (1+y\right )} = -\frac {3}{x^{2}} \]

1578

\[ {}y^{\prime } = \frac {3 x^{2}+2 x +1}{y-2} \]

1579

\[ {}\sin \left (x \right ) \sin \left (y\right )+\cos \left (y\right ) y^{\prime } = 0 \]

1580

\[ {}x y^{\prime }+y^{2}+y = 0 \]

1581

\[ {}\left (3 y^{3}+3 y \cos \left (y\right )+1\right ) y^{\prime }+\frac {\left (2 x +1\right ) y}{x^{2}+1} = 0 \]

1582

\[ {}x^{2} y y^{\prime } = \left (y^{2}-1\right )^{{3}/{2}} \]

1583

\[ {}y^{\prime } = x^{2} \left (1+y^{2}\right ) \]

1584

\[ {}\left (x^{2}+1\right ) y^{\prime }+x y = 0 \]

1585

\[ {}y^{\prime } = \left (x -1\right ) \left (y-1\right ) \left (y-2\right ) \]

1586

\[ {}\left (y-1\right )^{2} y^{\prime } = 2 x +3 \]

1587

\[ {}y^{\prime } = \frac {x^{2}+3 x +2}{y-2} \]

1588

\[ {}y^{\prime }+x \left (y^{2}+y\right ) = 0 \]

1589

\[ {}\left (3 y^{2}+4 y\right ) y^{\prime }+2 x +\cos \left (x \right ) = 0 \]

1590

\[ {}y^{\prime }+\frac {\left (1+y\right ) \left (y-1\right ) \left (y-2\right )}{1+x} = 0 \]

1591

\[ {}y^{\prime }+2 x \left (1+y\right ) = 0 \]

1592

\[ {}y^{\prime } = 2 x y \left (1+y^{2}\right ) \]

1593

\[ {}y^{\prime } \left (x^{2}+2\right ) = 4 x \left (y^{2}+2 y+1\right ) \]

1594

\[ {}y^{\prime } = -2 x \left (y^{3}-3 y+2\right ) \]

1595

\[ {}y^{\prime } = \frac {2 x}{1+2 y} \]

1596

\[ {}y^{\prime } = 2 y-y^{2} \]

1597

\[ {}x +y y^{\prime } = 0 \]

1598

\[ {}y^{\prime }+x^{2} \left (1+y\right ) \left (y-2\right )^{2} = 0 \]

1599

\[ {}\left (1+x \right ) \left (x -2\right ) y^{\prime }+y = 0 \]

1600

\[ {}y^{\prime } = \frac {1+y^{2}}{x^{2}+1} \]